The Research Progress of PD-1/PD-L1 Inhibitors Enhancing Radiotherapy Efficacy - Wen, Lu; Tong, Fan; Zhang, Ruiguang; Chen, Lingjuan; Huang, Yu; Dong, Xiaorong (Frontiers in Oncology, 2021)
PD-1/PD-L1 inhibitor has been approved for the treatment of various tumours. Research on how to improve radiotherapy efficacy using PD-1 / PD-L1 inhibitor is gaining momentum. Various studies have reported the survival benefits of the combined application of radiotherapy and PD-1 / PD-L1 inhibitor. However, radiotherapy is a double-edged sword for PD-1/PD-L immunotherapy. To fully exerts the immune activation effect of radiotherapy, while avoiding the immunosuppressive effect of radiotherapy as much as possible, the dose selection, segmentation mode, treatment timing and the number of treatment sites of radiotherapy play a role. Therefore, we aim to review the effect of radiotherapy combined with anti-PD-1/PD-L1 on the immune system and its optimization.